Household level Grey Water Treatment in Irbid Area in the North of Jordan - Bakheet, Wafaa Ahmed (Journal of natural sciences, life and applied sciences, 2020)
One of the means of meeting the water needs in the areas of scarcity is the reuse of greywater generated at the household level. This is water that comes out of the kitchen, bathtubs, washing machines and dishes. The water that coming out of the toilets is black water. This study aims to evaluate the potential of greywater availability in Irbid Area in the north of Jordan, by testing and comparing between greywater quality before and after household level treatment using a vertical multi-layer filter of sand and gravel then, reuse it for home gardens. Total greywater generation from different household sources were measured by water meters in five selected household during summer and winter. The physical, chemical and biological analysis of the samples revealed that greywater contains significant levels of suspended solid, chemical &biochemical oxygen demands, and inorganic compounds. Statistical analysis results indicated that there is a various removal percentage of the above parameters. Experimental results indicate that the percentage removal of BOD5 is 37.5%, the percentage removal of COD is 10%, the percentage removal of TDS is 68%, and a small decrease in pH value about 5%. The generation rates of greywater are mostly influenced by lifestyle and climatic conditions. Contaminants found in greywater are largely associated with the type of detergent used and influenced by other household practices. It is recommended to apply the Restricted irrigation that means irrigation of all types of crops with treated greywater except vegetables and plants including edible parts that can get in direct contact with irrigation water wither these parts are eaten raw or cooked.